Pengaruh Gaya Kepemimpinan Transformasional terhadap Tata Kelola Pembelajaran PAUD Di Kecamatan Cakranegara - Purnamasari, Tania; Nurhasanah; Sativa, Filsa Era (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study focuses on examining the impact of transformational leadership style on early childhood education (PAUD) learning management in the Cakranegara region. The research employed a quantitative correlational method. The sample consisted of 51 randomly selected instructors, while the total population comprised 76 PAUD teachers. Data were collected using a closed-ended Likert-scale questionnaire. The data were analyzed using SPSS 25 through t-tests, simple linear regression, and Pearson correlation analysis. With a correlation coefficient of 0.773 and a significance level of 0.000, the findings demonstrate a strong relationship between learning management and transformational leadership style. Based on the results of the simple linear regression test, 59.7% of learning management is influenced by transformational leadership. The alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected, as the t-test shows a value of 8.517, which exceeds the t-table value of 1.676 with a significance level of 0.000 (< 0.05). These findings indicate that PAUD learning management in Cakranegara District is significantly influenced by transformational leadership.